Building Independence and Innovation: Challenges of Entrepreneurship Education in Vocational High Schools - Sudiyono Sudiyono; Noor Soeseno Vijaya Krishna Nanji; Etty Sisdiana; Ika Mustika; Heru Setyono; Slamet Wibowo; Sulhi Sulhi (Yayasan Adra Karima Hubbi, 2024)
Entrepreneurship education in Vocational High Schools (SMK) is crucial for equipping students with practical skills and soft skills needed to be self-reliant and innovative in pursuing job opportunities or creating their own businesses. However, despite the implementation of entrepreneurship education, many SMK graduates have yet to succeed in becoming independent and innovative entrepreneurs. Previous research has primarily focused on curriculum development, teaching methods, and the role of educators, with limited attention to how students’ perceptions of entrepreneurship education impact their success as entrepreneurs. This issue reveals a gap between the delivery of entrepreneurship education and students' readiness to apply this knowledge in real-world scenarios. This study aims to analyze the perceptions of SMK Tourism students toward entrepreneurship education and its implications for entrepreneurial capabilities, as well as to identify barriers hindering the development of entrepreneurial spirit. The study adopts a mixed-methods approach, combining qualitative and quantitative methods with descriptive analysis. The qualitative approach includes in-depth interviews with teachers, principals, and alumni from four SMK Tourism schools in Jakarta, along with observations of infrastructure and cooking practice activities. Quantitative data were collected through a Google Form-based questionnaire survey targeting students from 13 SMK Tourism schools with a focus on Culinary Arts. The study results show that while most students hold positive perceptions of entrepreneurship education, challenges such as knowledge gaps, learning intensity, financial limitations, mental and emotional preparedness, entrepreneurship materials, collaboration and communication skills, and marketing and location barriers are the main obstacles for students aiming to become self-reliant entrepreneurs.